2000
DOI: 10.1177/104345420001700211
|View full text |Cite
|
Sign up to set email alerts
|

An International Study of Decision Making in Pediatric Oncology

Abstract: With therapeutic and supportive care options increasing in number and differing in nature in pediatric oncology, parents, patients, and healthcare providers are encountering multiple decision points during the course of treatment. Understanding the decision-making process experienced by the patient and parent will help healthcare professionals to better assist them and each other with the decision making and its aftermath. The purpose of this international feasibility study was to explore similarities and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
76
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(78 citation statements)
references
References 0 publications
2
76
0
Order By: Relevance
“…When making a decision about a treatment protocol in pediatric oncology, parents are faced with a tragic, unwanted choice between potentially lifesaving and toxic treatment or death. 11,12 This situation is likely to produce feelings of powerlessness, which may translate into decreased control over specific decisions. In contrast, parents making 26,27 An examination of these complex relationships is an important next step, because the ethical imperative of beneficence may be best achieved by helping parents to reach their desired level of control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When making a decision about a treatment protocol in pediatric oncology, parents are faced with a tragic, unwanted choice between potentially lifesaving and toxic treatment or death. 11,12 This situation is likely to produce feelings of powerlessness, which may translate into decreased control over specific decisions. In contrast, parents making 26,27 An examination of these complex relationships is an important next step, because the ethical imperative of beneficence may be best achieved by helping parents to reach their desired level of control.…”
Section: Discussionmentioning
confidence: 99%
“…In prior qualitative research parents of children with cancer reported feelings of shock and distress that impaired their decision-making about treatment 8 and research participation. 9,10 Parents reported feeling pressured to agree with physicians regarding treatment 8 and perceived few alternatives with respect to treatment 11,12 or clinical trial enrollment. 9 A number of demographic and contextual factors may relate to voluntariness, including demographic characteristics such as gender, 13 race, 14 education, 15 and income; 2,16 previous experience with a similar decision; time since diagnosis; parents' concern that the child' s care could be negatively affected or the medical team would be upset if the parent declines; 4,17 others'attempts to coerce, pressure, or manipulate the decision; 18 time pressure; 8,13,19 and the amount of information provided (too much or too little).…”
mentioning
confidence: 99%
“…When making a decision about a treatment protocol in pediatric oncology, parents are faced with a tragic, unwanted choice between potentially lifesaving and toxic treatment or death. 11,12 This situation is likely to produce feelings of powerlessness, which may translate into decreased control over specific decisions. In contrast, parents making 26,27 An examination of these complex relationships is an important next step, because the ethical imperative of beneficence may be best achieved by helping parents to reach their desired level of control.…”
Section: Discussionmentioning
confidence: 99%
“…In prior qualitative research parents of children with cancer reported feelings of shock and distress that impaired their decision-making about treatment 8 and research participation. 9,10 Parents reported feeling pressured to agree with physicians regarding treatment 8 and perceived few alternatives with respect to treatment 11,12 or clinical trial enrollment. 9 A number of demographic and contextual factors may relate to voluntariness, including demographic characteristics such as gender, 13 race, 14 education, 15 and income; 2,16 previous experience with a similar decision; time since diagnosis; parents' concern that the child' s care could be negatively affected or the medical team would be upset if the parent declines; 4,17 others'attempts to coerce, pressure, or manipulate the decision; 18 time pressure; 8,13,19 and the amount of information provided (too much or too little).…”
mentioning
confidence: 99%
“…Another study involving 43 parents suggested that parents fear disagreeing with health care workers over medical decisions concerning end-of-life care for their children. 6 In their recent study published in CMAJ, Tomlinson and colleagues add to the scant information available on end-of-life decision-making for children and pediatric palliative care. 7 The purpose of their study was to compare preferences for end-of-life treatment between health care workers and parents of children who were not expected to survive.…”
mentioning
confidence: 99%